Coral and Reef Fish Biodiversity in the Waters of Bangka Island, North Sulawesi - Mantiri, Rose O. S. E.; Septianto, Andarum; Ridwan, Moh.; Suputri, Putu Ayu; Podung, Thania Theresia; Kalmareuro, Vennda Uno; Sumilat, Deiske A. (Sam Ratulangi University, 2026)
This study documents and identifies the diversity of coral reefs and reef fish species in the waters of Bangka Island, North Sulawesi, a coastal area rich in marine biodiversity and ecologically and economically important to the local community. The Underwater Visual Census (UVC) method was used through snorkeling and diving at depths of less than 18 meters at three locations (Coral Eye house reef, Tanjung Husi, and Linggua) from March 14 to April 4, 2025. Visual data were collected and identified in the Coral Eye Library. The results indicate that the coral reef ecosystem around Coral Eye is dominated by branching corals (Acropora) and stony corals (massive), which are important habitats for reef fish. The reef fish community is dominated by the families Pomacentridae and Chaetodontidae at depths of less than 20 meters. Fish were grouped into indicator fish (family Chaetodontidae with 6 species), target fish (5 families with 10 species, including Serranidae, Mullidae, Siganidae, Labridae, and Scaridae), and major groups (14 families with 34 species). This study provides strategic recommendations for maintaining and preserving coral reef ecosystems and reef fish diversity on Bangka Island. Keywords: Coral reefs; Reef fish; Bangka Island Abstrak. Penelitian ini mendokumentasikan dan mengidentifikasi keanekaragaman terumbu karang dan spesies ikan karang di perairan Pulau Bangka, Sulawesi Utara, sebuah kawasan pesisir yang kaya akan keanekaragaman hayati laut dan penting secara ekologis serta ekonomis bagi masyarakat setempat. Menggunakan metode Underwater Visual Census (UVC) melalui snorkeling dan penyelaman pada kedalaman kurang dari 18 meter di tiga lokasi (Coral Eye house reef, Tanjung Husi, dan Linggua) dari 14 Maret hingga 4 April 2025. Data visual dikumpulkan dan diidentifikasi di Perpustakaan Coral Eye. Hasil penelitian menunjukkan bahwa ekosistem terumbu karang di sekitar Coral Eye didominasi oleh terumbu karang bercabang (Acropora) dan terumbu karang batu (massive), yang merupakan habitat penting bagi ikan karang. Komunitas ikan karang didominasi oleh famili Pomacentridae dan Chaetodontidae pada kedalaman kurang dari 20 meter. Ikan dikelompokkan menjadi ikan indikator (famili Chaetodontidae dengan 6 spesies), ikan target (5 famili dengan 10 spesies seperti Serranidae, Mullidae, Siganidae, Labridae, dan Scaridae), dan kelompok major group (14 famili dengan 34 spesies). Penelitian ini memberikan rekomendasi strategis untuk menjaga dan melestarikan ekosistem terumbu karang dan keanekaragaman ikan karang di Pulau Bangka. Kata kunci: Terumbu karang; Ikan karang; Pulau Bangka